Maturation of the Pupil Light Reflex Occurs Until Adulthood in Mice - Kircher, Noémie; Crippa, Sylvain V.; Martin, Catherine; Kawasaki, Aki; Kostic, Corinne (Frontiers in Neurology, 2019)
With respect to photoreceptor function, it is well known that electroretinogram (ERG) amplitudes decrease with age, but to our knowledge, studies describing age-related changes in the pupil light response (PLR) of mice are lacking. This study recorded the PLR and ERG in C57BL/6 and Sv129S6 wild-type mice at three different ages during early adulthood. Dark- and light-adapted PLR and ERG measurements were performed at 1, 2, and 4 months of age. For PLR measurements, we used either a red (622 nm) or blue (463 nm) light stimulus (500 ms) to stimulate one eye. We selected various light intensities ranging across almost 4 log units and subsequently classified them as low, medium, or high intensity. From the recorded PLR, we selected parameters to quantify the early and late phases of the response such as the baseline pupil size, the maximal constriction amplitude, the maximal velocity, the early partial dilation (area under the curve of the positive peak of the first derivative of PLR tracing), and the sustained constriction amplitude. For ERG measurements, both scotopic and photopic responses were recorded following stimulation with green light (520 nm) at preselected intensities. The amplitudes and latencies of the a-wave and the b-wave were also analyzed. In both strains, 1-month-old animals presented with a smaller baseline pupil diameter compared to that in 2- and 4-month-old mice. They also exhibited greater maximal constriction amplitude in response to red stimuli of medium intensity. Further, 1-month-old Sv129S6 mice responded with greater constriction amplitude to all other red and blue stimuli. One-month-old C57BL/6 mice also demonstrated faster early partial dilation and smaller sustained response to low blue stimuli. The ERG of 1-month-old C57BL/6 mice showed a greater scotopic a-wave amplitude compared to that of 2-month-old mice, whereas no significant differences were found in Sv129S6 mice. These results suggest that the functional maturation of the neuronal pathway that mediates the PLR continues after 1 month of age. In studies that measure PLR to determine retinal integrity in adult mice, it is thus important to determine normative values in animals of 2 months of age.